The relationship between physical exercise and subjective well-being in Chinese older people: The mediating role of the sense of meaning in life and self-esteem - Chen, Rui; Liu, Yong-Feng; Huang, Gao-Duan; Wu, Peng-Cheng (Frontiers in Psychology, 2022)
Purpose：This study explores the relationship between physical exercise and older people's subjective well-being and the mediating role of a sense of meaning in life and self-esteem by using a structural equation modelling (SEM) approach, in order to provide some suggestions for improving older people's subjective well-being. Results: Physical exercise was able to have a positive effect on the level of subjective well-being of older adults (β=0.0305; 95% confidence interval (CI): 0.0226, 0.0384; p<0.05), and a mediation analysis of sense of meaning in life and self-esteem revealed that they were able to have independent and chained mediation effects, with four pathways: first, physical exercise directly affected subjective well-being of older adults (β=0.0149; 95% CI: 0.0072, 0.0226; p<0.05) (β=0.0149; 95% CI: 0.0072, 0.0226; p<0.05); secondly, sense of meaning in life mediated the relationship between physical exercise and subjective well-being of older adults (β=0.0075; 95% CI: 0.0041, 0.0115; p<0.05); thirdly, self-esteem mediated the relationship between physical exercise and subjective well-being of older adults (β=0.0075; 95% CI: 0.0041, 0.0115; p<0.05). (β=0.0061; 95% CI: 0.0034, 0.0094; P<0.05); fourth, a chain mediating effect of sense of meaning in life and self-esteem in the relationship between physical exercise and subjective well-being in older adults (β=0.0021; 95% CI: 0.0010, 0.0035; P<0.05). Conclusions and prospects: As indicated by the results, physical exercise can enhance the subjective well-being of older adults through sense of meaning in life and self-esteem, therefore, in order to be able to enhance the subjective well-being of older adults, enhancing the level of sense of meaning in life and self-esteem of older adults is an effective means.